Characterization of milk production in small properties in the Western Border of the state of Rio Grande do Sul (Research, Society and Development, 2022)
The objective was to evaluate attributes related to the quality control of milk production in the municipality of Santana do Livramento, located in the Western Border region of the state of Rio Grande do Sul (RS). Characteristics comprise the physicochemical and microbiological properties of locally produced milk, as well as the management of cattle during and after milking. The research instruments were interviews and questionnaires applied to milk producers in the interior of the municipality, as well as professionals who work in the area of dairy production. The reality of family producers on the production scale and hygiene processes at the time of production demonstrated a need to comply with practices in order to generate compliance with current legislation. In this context, the need for good production practices (GPP) was observed to increase compliance with Normative Instruction 76 (IN-76) of the Ministry of Agriculture, Livestock and Supply (MALS).